Effect of frequency of sensor use on glycaemic control in individuals on sensor-augmented pump therapy with and without Predictive Low Glucose Management System. (January 2020) - Abraham, Mary B.; Smith, Grant J.; Nicholas, Jennifer A.; Fairchild, Janice M.; King, Bruce R.; Ambler, Geoffrey R.; Cameron, Fergus J.; Davis, Elizabeth A.; Jones, Timothy W.; ,
Abstract: Improved frequency of sensor use improves glycaemic control. Furthermore, there is no deterioration of glycaemic control with increased sensor use in individuals on Predictive Low Glucose Management (PLGM) system. Younger children are more likely to have better sensor uptake than older children.